Kompensasi, Disiplin Kerja, dan Motivasi terhadap Produktivitas Karyawan - Nur Augus Fahmi; Irene Anggie Angelia Rajaguguk; Laura Ike Selya Br Simorangkir; Iis Anggela (IPM2KPE, 2023)
This study aims to determine and reveal the effect of employee incentives, work routines, and workplace regulations on results at PT. Archipelago Rubber Industry. This research method is quantitative. The population of the total study consisted of 82 workers at PT. Nusantara Rubber Industry and 68 employees of PT. Archipelago Rubber Industry. Multiple linear regression analysis is a technique used in the research process. The results showed, a) the feeling value was higher than the table, or 7.224 higher than 1.983, with a significance of 0.044 0.05; b) the discipline score is lower than the table, or 863 lower than 1.983; c) the value of work motivation is lower than the table, namely -684 with a significance of 0.497 less than 0.05. As a result, Ftable (2.69) is greater than Fcount (1.724), so the number is 0.171 > 0.05. conclusions, sanctions, discipline, and motivation all have an indirect and synchronous beneficial impact on PT. Nusantara Rubber Industry Output (rubber sales company). Keywords: Work Discipline, Compensation, Motivation, Employee Productivity